2019
DOI: 10.18805/ijar.b-3786
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters and Animal Model Evaluation of First Lactation 305-d Milk Yield and Energy Traits in Karan Fries Cattle

Abstract: First lactation records of 351 Karan-Fries cows born to 27 bulls, having 3 or more progeny were used to evaluate sires by animal model (AM). Heritabilities, genetic and phenotypic correlations between the traits were estimated by univariate and bivariate linear animal models. The heritability estimates for 305 days or less milk yield (305MY), fat based energy corrected milk yield (FECMY), fat protein based energy corrected milk yield (FPECMY) and fat protein lactose based energy corrected milk yield (FPLECMY) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
2
2
1
Order By: Relevance
“…The overall least squares averages for first to tenth monthly yields were estimated as 313.92,347.53,337.36,323.32,305.50,288.26,269.47,236.35,229.84 and 158.23 kg, in the first lactation of Frieswal cows. The average yields obtained for different months were nearer to the values reported by Singh (2006) in Karan Fries cattle. However, the monthly averages obtained in the present study were higher than the estimates reported by Kumar (1990), Varshney and Tomar (1982), Shrivastava and Khan (1987), Raja (2012) and Mundhe et al (2015) in Sahiwal cattle.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…The overall least squares averages for first to tenth monthly yields were estimated as 313.92,347.53,337.36,323.32,305.50,288.26,269.47,236.35,229.84 and 158.23 kg, in the first lactation of Frieswal cows. The average yields obtained for different months were nearer to the values reported by Singh (2006) in Karan Fries cattle. However, the monthly averages obtained in the present study were higher than the estimates reported by Kumar (1990), Varshney and Tomar (1982), Shrivastava and Khan (1987), Raja (2012) and Mundhe et al (2015) in Sahiwal cattle.…”
supporting
confidence: 72%
“…significant effect of AFC on second to sixth individual monthly yields in Sahiwal cattle. The significant influence of AFC on different monthly yields was also reported by Varshney and Tomar (1982), Shrivastava and Khan (1987), Kumar (1990), Qureshi et al (1995), Gaur (1996), Singh (2006) and Raja (2010). However, Roy et al (2001) reported non-significant regression of monthly milk yields on AFC in HF cattle.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Hertitability of various traits studied were presented in Table 3. The Heritability estimates for 305 DLMY yield was 0.40±0.16, which is higher than the reports of Singh et al (2020). The total LMY was moderate (0.31± 0.14) which is higher than the reports of Singh et al (2008) and Vinoo et al (2005) in Ongole cattle.…”
Section: Heritabilitycontrasting
confidence: 56%
“…The usefulness of test day milk yields and peak yield depends on the estimation of genetic parameters like heritability of these records, and genetic and phenotypic correlations amongst these records and with FL305DMY. The estimation of genetic parameters plays an important role in determining the appropriate method of selection to predict direct and correlated response to selection, and formulating optimum breeding strategies for future genetic improvement of dairy animals (Singh et al, 2020;Jamuna et al, 2015;Godara et al, 2015;Pareek and Narang, 2014). Information on genetic parameters estimates of monthly test day milk yields and peak yield records of buffaloes is scanty to date, therefore, the present investigation was conducted to assess the genetic parameters for monthly test day milk yields, peak yield and first lactation 305 days milk yield in Murrah buffaloes.…”
Section: Introductionmentioning
confidence: 99%